What Proportion of Preschool‐Aged Children Consume Sweetened Beverages?. (March 2014) - Nickelson, Jen; Lawrence, Jeannine C.; Parton, Jason M.; Knowlden, Adam P.; McDermott, Robert J.
ABSTRACT BACKGROUND Obesity affects nearly 17% of US children and youth 2‐19 years old and 10% of infants and toddlers under the age of 2 years. One strategy for addressing obesity is to discourage sugar‐sweetened beverage (SSB) consumption. Compared with their older school‐aged counterparts, children ≤5 years depend largely on parents for the purchase and serving of SSBs. Therefore, recognizing parental factors associated with children's intake of SSBs is important. METHODS This study used cross‐sectional data from parents of children ≤5 years old to examine SSB consumption and associated factors. Elements of the Health Belief Model and Theory of Reasoned Action facilitated data analysis and interpretation. RESULTS The most consistent predictor of SSB intake was child age. Nearly 94% of children aged 3‐5 years consumed sweetened milk products, 88% consumed fruity drinks, 63% consumed sodas, and 56% consumed sports drinks and sweet tea. Adjusting for all other factors, the only parental psychosocial factor associated with SSB intake was self‐efficacy (predicting fruity drinks consumption). CONCLUSIONS More children drink SSBs as they get older. Interventions designed to prevent SSB consumption should occur early, before children reach preschool age. Additional study of parental factors influencing SSB intake in early childhood is recommended.